2021
DOI: 10.15294/jpii.v10i4.31442
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Skill Laboratory Activities: How to Improve Students’ Scientific Communication and Collaboration Skills

Abstract: This study aims to analyze the effects of experiment models and gender on scientific communication and collaboration skills. This study employed a quasi-experimental design consisting of five groups as control classes and five groups as experimental classes. The subject of this study was 327 students (168 students used HOT Lab and 159 used Multiple Skill; 69 Male and 258 Female from 18 to 22 years old) with heterogeneous skills and learning habits from five different universities representing four regions: Sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…This social construction theory emphasizes that human intelligence comes from society, environment and culture. The theory of cognitive socio-cultural also asserts that individual cognitive acquisition occurs first through interpersonal (interaction with the social environment) intrapersonal (internalization that occurs within oneself) (Malik & Ubaidillah, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This social construction theory emphasizes that human intelligence comes from society, environment and culture. The theory of cognitive socio-cultural also asserts that individual cognitive acquisition occurs first through interpersonal (interaction with the social environment) intrapersonal (internalization that occurs within oneself) (Malik & Ubaidillah, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, students are expected to be able to relate it in everyday life so that students are proficient in dealing with problems or phenomena in real life that require students to think. Students can form knowledge through interactions that occur during collaborative practicum activities (Malik, & Ubaidillah, 2021). Critical thinking skills can be developed through investigation activities in science laboratories .…”
Section: Resultsmentioning
confidence: 99%
“…The high result of argumentation skills in virtual laboratory activities is because virtual laboratories are considered easier to use and can also be efficient time (Potkonjak et al, 2016). In addition, previous research revealed that using a virtual laboratory can make students more quickly find evidence to meet evidence in argumentation skills (Malik & Ubaidillah, 2021;Putra et al, 2021). Other previous studies also revealed that using a real laboratory will take more time than using a virtual laboratory, so when students do backing, it will be easier to do virtual laboratory activities than real laboratory activities (Roviati et al, 2017).…”
Section: Resultsmentioning
confidence: 99%